ثقــــــــــــافـــــــة الفــــــــــــقر من منظور أنثروبولوجي تنـــــــــــــــموي - بن محمــــــــــدد .جميــــــلة الــهــادي مفتــــــاح (Aljameai)
Abstract: The study aimed to identify the culture of poverty from a developmental anthropological perspective as one of the topics of interest to development anthropology, to contribute to development processes. The study was divided into three parts, the first part dealt with the concept of the culture of poverty from an anthropological perspective, while the second part dealt with the concept of poverty from a developmental perspective, while the third part dealt with the culture of poverty from an anthropological and developmental perspective, and in the context of these parts and then reviewing concepts related to the culture of poverty. As the concept of poverty, and its most important distinguishing characteristics, as well as what development is, its philosophy, its importance, and exposure to poverty as one of the obstacles to development, leading to an indication of poverty measures and its main causes, and the study used the descriptive approach to suit the nature of the subject under study